Osnovaniia iuridicheskoi otvetstvennosti - Moiseeva A. A. (Students' science: current realities, 2017)
In recent years, the Republic of Belarus has been rapidly and broadly developed legislation aimed at implementing the principles of the rule of law and the implementation of fundamental changes in various spheres of public life. In this regard, there is a need to improve the institution of legal liability.
Keywords: юридическая ответственность; правонарушение; социальная ответственность; social responsibility; общественная жизнь; public life; основания ответственности; legal responsibility; grounds for liability; offense